Deadly Performance of Hegemonic Masculinity: A Study of Jeffrey Dahmer - Phattika, Adhysti Keinar (CV. Tripe Konsultan, 2025)
This research examines the portrayal of masculinity in Dahmer – Monster: The Jeffrey Dahmer Story (2022), emphasizing on how Jeffrey Dahmer performs hegemonic masculine traits despite his marginalized sexual identity. Using a qualitative textual analysis method, this research applies R.W. Connell’s theory of hegemonic masculinity and Judith Butler’s theory of gender performativity to analyze key scenes depicting Dahmer’s criminal acts. This study found that Dahmer consistently embodies hegemonic masculine traits, such as domination, control, and power, as well as the objectification of the others. His murdering acts are not isolated events, but rather ritualized performances that reaffirm masculine dominance through repeated acts of violence. Despite his queerness puts him outside the heteronormative masculinity, it does not subvert the patriarchal structure, in fact, it coexists with it through his acts. This study highlights the adaptability of hegemonic masculinity across different heteronormative sexual identities and challenges the assumption that queerness inherently resists dominant gender norms. The implications extend to the fields of gender studies, media studies, true crime narratives, and criminology studies, urging scholars and audiences to reconsider the intersection of queerness, race, and masculinity in representation of crime narrative. Future research is encouraged to explore further on the audiences’ reception toward perpetrators across diverse identity and cultural context.